1988
DOI: 10.1016/0035-9203(88)90187-3
|View full text |Cite
|
Sign up to set email alerts
|

The effect of mefloquine-artemether compared with quinine on patients with complicated falciparum malaria

Abstract: 30 pairs of patients with complicated Plasmodium falciparum malaria (with anaemia, hyperpyrexia, jaundice or more than 5% of erythrocytes parasitized) were studied. Patients with cerebral signs and symptoms were excluded. One group of patients was treated with oral mefloquine (750 mg) and artemether (600 mg by injection, 200 mg initially and 100 mg every 12 h). The second group of patients was treated with quinine (10 mg/kg orally every 8 h for 7 d). All patients were admitted to hospital for 7 d and examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…Drugs for chloroquine-resistant malaria are quinine, sulfadoxine-pyrimethamine combination, mefloquine, artesunate and its derivatives, halfantrine and certain antibiotics. [21] This is a hospital based study representing only tip of iceberg of the patients of malaria in community. This study was done in admitted patients in the tertiary care center.…”
Section: Discussionmentioning
confidence: 99%
“…Drugs for chloroquine-resistant malaria are quinine, sulfadoxine-pyrimethamine combination, mefloquine, artesunate and its derivatives, halfantrine and certain antibiotics. [21] This is a hospital based study representing only tip of iceberg of the patients of malaria in community. This study was done in admitted patients in the tertiary care center.…”
Section: Discussionmentioning
confidence: 99%
“…This could be due to thick blood films for asexual parasitaemia being taken every 12 hours, whereas other studies took them every four hours, every six hours, and then every 12 hours. The accuracy of parasite clearance has been shown to improve with frequent (four to six hourly) measurement of parasitaemia 1113. The parasite clearance time after oral, intramuscular, or rectal artemether is shorter in patients with uncomplicated malaria than in those with complicated malaria 14…”
Section: Discussionmentioning
confidence: 99%
“…The reason for the lower death rate with artemether is not clear. Several trials in south east Asian adults with severe malaria indicated that treatment with artemesinin derivatives might halve mortality 12 13…”
Section: Discussionmentioning
confidence: 99%
“…Parasite clearance times, fever reduction times, and coma resolution times in general are improved for patients treated with AM or AS relative to those for patients treated with standard antimalarial treatment regimens (18,21,22,28,29,31,33). Early recrudescence of parasites, however, has necessitated either multidrug chemotherapy or increasingly higher doses of AM and AS (22).…”
mentioning
confidence: 99%